Moderate toxicity with late onset as a good omen: association between toxicity and survival in the checkpoint inhibitor immunotherapy—a single center experience - Rudzińska, Anna; Juchaniuk, Pola; Oberda, Jakub; Krukowska, Kamila; Krzyśkowska, Sylwia; Kuchta, Eliza; Rodzajewska, Anna; Janiszewska, Mariola; Machulska-Ciuraj, Katarzyna; Szklener, Katarzyna (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy by enhancing T-cell-mediated immune responses against tumors. However, their use can lead to immune-related adverse events (irAEs) impacting patient outcomes. This single-center, observational study investigates the relationship between immune-related adverse events (irAEs) and survival outcomes and, to our knowledge, is the first of this kind in Polish population. Data of the 151 patients treated with ICIs, with or without chemotherapy, at the Department of Clinical Oncology and Chemotherapy in the Independent Public Hospital No. 4 in Lublin were collected from electronic medical records. Statistical analyses were performed using the Kaplan–Meier estimator, log-rank test, and multivariable Cox proportional hazard model (p < 0.05). IrAEs were observed in 38% of the patients, with the most common being thyroid dysfunction (11.9%) and dermal toxicity (6.6%). The median OS for patients with irAEs was 18.7 months, compared to 13.6 months for those without irAEs, though the difference was not statistically significant (p = 0.284). Patients with moderate toxicity had the highest median OS (26 months), while those with severe toxicity had a median OS of 6.41 months. Late-onset irAEs were associated with improved OS and PFS. Pack-years of smoking significantly impacted both OS (HR = 1.01, p = 0.014) and PFS (HR = 1.01, p = 0.011). Despite results not reaching statistical significance, the findings emphasize the clinical relevance of irAEs in treatment optimization and warrant further research to better understand their role in patient outcomes.